Fuel and fire characteristics in savanna–woodland of West Africa in relation to grazing and dominant grass type - Savadogo, P.; Zida, D.; Sawadogo, L.; Tiveau, D.; Tigabu, M.; Oden, P.C. (2007)
Fuel characteristics, fire behaviour and temperature were studied in relation to grazing, dominant grass type and wind direction in West African savanna–woodland by lighting 32 prescribed early fires. Grazing significantly reduced the vegetation height, total fuel load, and dead and live fuel fractions whereas plots dominated by perennial grasses had higher values for vegetation height, total fuel load and the quantity of live fuel load. Although fire intensity remained insensitive (P>0.05) to any of these factors, fuel consumption was significantly (P =0.021) reduced by grazing, rate of spread was faster in head fire (P =0.012), and flame length was shorter in head fire than back fire (P =0.044). The average maximum temperature was higher (P<0.05) on non-grazed plots, on plots dominated by annual grasses, on plots subjected to head fire, and at the soil surface. Lethal temperature residence time showed a nearly similar trend to fire temperature.Wind speed and total fuel load were best predictors of fire behaviour parameters (R2 ranging from 0.557 to 0.862). It can be concluded that grazing could be used as a management tool to modify fire behaviour, back fire should be carried out during prescribed burning to lower fire severity, and the fire behaviour models can be employed to guide prescribed early fire in the study area.